Socially responsible public procurement (SRPP) in multi-level regulatory frameworks: Assessment report on policy space for SRPP regulation and implementation in Germany and Kenya - Tim Stoffel (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Public Procurement is a highly regulated process ruled by a complex legal framework. It comprises not only national but also, increasingly, sub- and supranational regulations, giving rise to a multi-level regulatory governance of public procurement. The integration of sustainability aspects into public procurement, as called for in goal 12.7 of the Sustainable Development Goals (SDGs) of the Agenda 2030, needs to take this multi-level character into account. This reports focuses on social considerations, which are a central part of sustainable procurement - whether with a domestic focus or along international value chains. Social considerations have been somewhat neglected in Europe, whereas they feature prominently in procurement regulations in many countries of the Global South, especially in Sub-Saharan Africa (SSA) (see Stoffel, Cravero, La Chimia, & Quinot, 2019). The advanced process of regional integration in the European Union (EU) and the progress made towards integration in some regional economic communities in Sub-Saharan Africa call for deeper analyses of the influence of the higher levels of the regulatory framework on the lower levels, and the consequences of regulation. The question is whether public entities, from the national down to the local level, are required to integrate socially responsible public procurement (SRPP) into their procurement processes and tenders, or at least have the option to do so.
Keywords: 330; Öffentlicher Auftrag; Sustainable Development Goals; Vergaberecht; Föderalismus; Deutschland; Kenia